SISTEM INFORMASI INDEKS KEPUASAN MASYARAKAT DENGAN METODE PERBANDINGAN EKSPONENSIAL (MPE) DAN SKALA ORDINAL PADA UNIT PELAYANAN MASYARAKAT (Information Technology and Telematics, 2016)
As a provider of public services, community services unit faced with many issues related to improving the quality of public services through the performance of good service and products quality services. To measure the performance of the public service units, required elements / indicators as a reference to provide an assessment of the results of the performance of public service units, above it needed an information system to bring the results of an assessment of the performance of the service unit. Making the information system is to use exponential comparison method (MPE) and the ordinal scale,